Effect and extraction of series resistance in Al2O3‐InGaAs MOS with bulk‐oxide trap. Issue 7 (1st March 2013) - Yu, B.; Yuan, Y.; Chen, H.‐P.; Ahn, J.; McIntyre, P.C.; Taur, Y.
Abstract : The effect of parasitic series resistance in the accumulation region has been investigated under the framework of the distributed bulk‐oxide trap model. It is shown that while the series resistance may be too small to impact the total capacitance, it can have a significant effect on the total conductance by adding a term ∝ ω 2 . It leads to a proposal of an extraction method for series resistance. The enhanced bulk‐oxide trap model with series resistance as well as dielectric leakage can explain the uncommon conductance frequency dispersion data for an Al2 O3 ‐InGaAs MOS capacitor with 2.5 nm thin Al2 O3 layer.